Analysis Of Occupational Stress And Impact On Employee Performance In Hotels Of Varanasi ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Varanasi has an abundance of hotels that have been handling the demand of both Indian and Foreign  guests. As a result, the staff who works in Varanasi’s hotel faces severe hardship and that reduce their overall  performance and it results the occupational stress for all the sides. Hence the study was undertaken in context of  selected Varanasi hotels obtaining employee viewpoint of they perceived occupational stress and how does it impact  their performance. Objective: The study had three fold objectives. First, exploring the antecedents of occupational  stress from demographic perspective of hotel employees in Varanasi. Second, examining the impact of antecedents of  occupational stress on hotel employee performance. Thirdly, determining the relationship between occupational stress  and employee performance in context of Varanasi hotels. Methodology: The study used exploratory cum descriptive  research design following deductive research approach. A structured non-disguised questionnaire was designed to collect  data from 279 employees working in the Star and heritage hotels in Varanasi using non-probability purposive sampling.  Factor Analysis, Multiple Regression Analysis and Correlation Analysis were used to gather results using R software.  Result: The study extracted five antecedents for Occupational Stress based on admissible range of Eigen values that  contributed 61.915% of the total variance. These were Role Ambiguity, Workload, Interpersonal Relations, Career  Development and External Responsibilities. Further, four factors for employee performance were extracted. These were  Output Quality, Professional Competence, Result Orientation and Work Efficiency. The result from Multiple Regression  stated all factors of occupational stress significantly affect employee performance. The model explains 62.7% variability  of employee performance as dependent variable explained by independent variables. The results from correlation  analysis explained that Role ambiguity, Workload and External Responsibilities were negatively correlated, whereas  External Responsibilities and Career Development positively correlated with Employee performance. Conclusion: The study advocates adequate communication amongst co-workers will aid in eliminating conflicts originating from  external responsibilities, and sound communication down the management ensures reduced insecurities for career  progression. It provides the basis for hotels to evaluate their employee performance and suggestive measures to induce  their performance. The research on occupational stress in the hotel industry will provide a theoretical framework for  other service industries in context to employee performance in this and other industries.
Keywords: Hotels; Antecedents; Occupational Stress; Employee Performance; Varanasi